PENGARUH LAMA WAKTU PEMBERIAN PAKAN YANG MENGANDUNG BUAH MAHKOTA DEWA TERHADAP PERTUMBUHAN DAN IMUNITAS IKAN LELE YANG DIINFEKSI Aeromonas Hydrophila - Lili Suryati; Ade Dwi Sasanti; Mohamad Amin (Universitas Sriwijaya, 2017)
ABSTRACT One of the bacterial diseases that attacks freshwater fish is Motile Aeromonas Septicemia (MAS) caused by Aeromonas hydrophila. The aim of this research is to know the effect of different feeding time duration that contain Phaleria macrocarpa flour to prevent of A. hydrophila. Research was conducted from September until November 2016 on Laboratorium Budidaya Perairan, Faculty of Agriculture, Sriwijaya University and Laboratorium UPT Klinik Kesehatan. The research designed based on Completely Ranomized Design (CRD) with four treatments and three replications. Clarias sp. was given feed treatment for 14 days (P1), 21 days (P2), and 28 days (P3). Feed treatment in the form of flour Phaleria add to commercial feed as many as 1 gram from 100 grams of commercial feed. The parameters observed on this research were total leucocytes, hematocrit concentration, growth, prevalence, and survival. The result showed that the addition of P. macrocarpa flour on feed was to prevent infection caused A. hydrophila revaled by decreasing of prevalence of fish. The addition of Phaleria macrocarpa flour for 21 days is the best treatment, seen from the increasing total leucocytes and hematocrit concentration and produse survival of 86,67% and prevalence value of 32,68% after injected by A. hydophila bacteria.Keywords: Aeromonas hydrophila, Clarias sp., Phaleria macrocarpa